2005
DOI: 10.2139/ssrn.744244
|View full text |Cite
|
Sign up to set email alerts
|

Recent Competition in the Japanese Life Insurance Industry

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In this context, it is important to recognize that the Japanese insurance industry experienced severe industrial reorganization starting from the beginning of the 1990s. The high efficiency values found in our data might thus indicate efficiency improvements as a result of this reorganization process over the last 15 years (see Lai and Limpaphayom, 2003;Souma and Tsutsui, 2005 for the development of the Japanese insurance market; Amel et al (2004) report corresponding evidence for the Japanese banking market). The lowest efficiency values are found for the Philippines (average efficiency 0.22 in non-life).…”
Section: Technical Efficiencymentioning
confidence: 61%
“…In this context, it is important to recognize that the Japanese insurance industry experienced severe industrial reorganization starting from the beginning of the 1990s. The high efficiency values found in our data might thus indicate efficiency improvements as a result of this reorganization process over the last 15 years (see Lai and Limpaphayom, 2003;Souma and Tsutsui, 2005 for the development of the Japanese insurance market; Amel et al (2004) report corresponding evidence for the Japanese banking market). The lowest efficiency values are found for the Philippines (average efficiency 0.22 in non-life).…”
Section: Technical Efficiencymentioning
confidence: 61%
“…Souma and Tsutsui (2000) concluded that the degree of competition of the Japanese life insurance industry was low, although it has increased since 1995. On the other hand, Uchida and Tsutsui (2005) concluded that the Japanese city banks were subject to perfect competition in the mid-1990s.…”
Section: Discussionmentioning
confidence: 99%
“…Uchida and Tsutsui (2005) estimated the degree of competition in the Japanese banking sector from 1974 to 2000 using a new method. Souma and Tsutsui (2000) applied a similar method to the Japanese life insurance industry for the period 1986 to 1997.…”
Section: Introductionmentioning
confidence: 99%
“…1 Following Clark and Davies (1982), Alley (1993) estimated the degree of collusion in the Japanese banking sector to find a high degree of collusion in 1986 and 1987. Souma and Tsutsui (2000) applied an approach similar to that of this paper to the Japanese life insurance industry from 1986 to 1997 and found that the degree of competition was low, but that the industry became more competitive after 1995 when the New Insurance Industry Law was promulgated. Kamesaka and Tsutsui (2002) estimated Panzar-Rosse's H-statistic for the Japanese securities industry and found that the industry was in monopoly equilibrium in the 1980s and was in monopolistic competition equilibrium in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Souma and Tsutsui (2000) found that although competition in the Japanese life insurance industry became stronger after 1995, it was still close to perfect collusion in 1997. Kamesaka and Tsutsui (2002) found that the Japanese securities industry was in monopoly equilibrium in the 1980s and was in monopolistic competition equilibrium in the 1990s.…”
mentioning
confidence: 99%